Pengaruh Kompensasi Manajemen, Umur Perusahaan, Pertumbuhan Penjualan, Capital Intensity dan Leverage terhadap Penghindaran Pajak - Widyadhari Ramadhania Pramesti; Clara Susilawati (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This study aims to analyze and examine the effect of management compensation, firm age, sales growth, capital intensity and leverage on tax avoidance. In this study, tax avoidance is proxied using the Effective Tax Ratio (ETR). The data source used in this study uses secondary data in the form of company financial reports that have been published on the Indonesia Stock Exchange (IDX). The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The method of determining the sample used in this research is purposive sampling method. The samples used in this study were 72 manufacturing companies that have been listed on the Indonesia Stock Exchange (IDX). The data analysis technique used in this study is multiple linear regression which shows the results of the study that the variables of management compensation, capital intensity and leverage have an effect on tax evasion, while the firm age and sales growth variables have no effect on tax evasion. For future researchers who wish to conduct further research related to tax avoidance, it is better to add and extend the research period and add research objects to provide better results. Keywords: Management Compensation, Company Age, Sales Growth, Capital Intensity, Leverage, Tax Avoidance.